Analisis Kepuasan Cleaning Service dengan Menggunakan Metode Service Quality dan Importance Performance Analysis (IPA) pada Rsud. Prof. Dr. W. Z. Johanes Kupang - Here, Alfonsius Israel; Kleden, Maria Agustina; Atti, Astri (ESTIMASI: Journal of Statistics and Its Application, 2025)
Hospital is an organization run by professional medical personnel who are well organized in terms of medical infrastructure, continuous nursing care, and diagnosis and treatment of diseases suffered by patients. According to the system, hospitals are run by workers such as doctors, nurses, hospital employees, and also cleaners such as cleaning services. The purpose of this study was to determine the cleaning service satisfaction of Prof. Dr. W. Z. Johanes Kupang hospital as an important component of the implementation of activities in the hospital using the servqual and importance performance analysis (IPA) methods. The result of this study is that the cleaning service as a whole is dissatisfied with the hospital side because it is based on the results of calculating the gap or the difference between the expected and reality values, namely -14.30044.